The Role Of Ambition For Freedom In Entrepreneurship Education As Entrepreneurial Motivation - Siti Rahayuningsih; Sudarmiatin Sudarmiatin; Rizky Firmansyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Entrepreneurship plays a crucial role in advancing the Indonesian economy with the potential to reduce unemployment and support economic growth. Although the government intensively encourages the spirit of entrepreneurship, there are still obstacles, especially related to not daring to face business risks. Amid the pandemic, unemployment is rising, prompting some individuals to turn to self-employment as a way of surviving. However, the number of entrepreneurs in Indonesia is still below international standards, reflecting obstacles to stimulating entrepreneurial interest. Phenomenological research on the role of ambition for freedom as an entrepreneurial motivation among students and alumni of Commerce Education at State University of Malang is still limited. Further understanding of ambition for freedom in the context of entrepreneurial learning at universities is needed to inform effective educational strategies, encourage interest in entrepreneurship at the local level, and support national economic growth. This study used a descriptive qualitative approach. The subject of the study involves Students. Data was collected through observation, interviews, and documentation. Data analysis involves the reduction, display, and inference of data, with tringulation used to ensure validity. The results showed that comprehensively, the findings of the three data collection methods consistently supported the central role of Ambition for Freedom in motivating Commerce Education students to choose and succeed in entrepreneurial careers. These overall findings provide a deep understanding of the dynamics of intrinsic motivation in the context of entrepreneurial learning. This research provides a strong foundation for advanced research related to the development of entrepreneurial learning strategies that focus more on aspects of intrinsic motivation. In addition, longitudinal research can provide a clearer picture of the long-term impact of entrepreneurial learning on the careers of students and alumni.